Optimasi Kebutuhan Gizi Untuk Ibu Hamil Dengan Menggunakan Hybrid Algoritma Genetika dan Simulated Annealing - Binti Robiyatul Musanah; Wayan Firdaus Mahmudy; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Nutritional needs are very necessary for pregnant women. Good nutrition is balanced nutrition and according to needs. If the needs of pregnant women are not suitable can experience Chronic Energy Deficiency with these problems, a system is needed to fulfill the nutrition of pregnant women who can provide solutions in the form of food ingredients in accordance with the method of Hybrid Genetic Algorithms and Annealing Simulation. In the process of solving this problem at Simulated Annealing or Genetic Algorithm. This hybrid process is in a crossover process using a single intersection, mutation insertion for the mutation process and the use of elits in the selection and simulation of Annealing. The previous test results obtained parameters with the Hybrid GA and SA method obtaining the best parameter value which is equal to 100 (population size) fitness which obtained an average of 0.06268, the value of 105 (generation) obtained by average fitness0. 06823, i 4 with a fitness value of 0.6, the average is 0.06792, and the average temperature with a value of 1 and apha is 0.5 obtained by the best fitness with an average of 0.06800 along with 0.08876. The hybridization suitability of GA and SA reached 0.08804 higher than the average GA suitability value of 0.05519 and SA suitability which was 0.04382 with a specified time of 1 minute and the requirements generated from the system were insufficient for the nutritional needs of the pregnant women.